2020
DOI: 10.1155/2020/9496564
|View full text |Cite
|
Sign up to set email alerts
|

Vaping Is Not Safe: A Case of Acute Eosinophilic Pneumonia following Cannabis Vapor Inhalation

Abstract: There is a well-established association between inhalational exposures and acute eosinophilic pneumonia (AEP). The most reported exposure is cigarette smoking. Here, we present a case of progressive shortness of breath and nonproductive cough in a college student with no significant medical history, approximately 10 days after inhaling cannabis aerosols on two separate occasions. He was started on empiric antibiotics and bronchodilators without improvement. He was diagnosed with AEP based on peripheral eosinop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Nevertheless, the laboratory-based results of the current investigation showed that salivary immunoinflammatory response is worse in CS and ENDS users than non-smokers. This outcome supports previous studies [ 38 , 39 ] that have shown that vaping is by no means a safe replacement for smoking.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the laboratory-based results of the current investigation showed that salivary immunoinflammatory response is worse in CS and ENDS users than non-smokers. This outcome supports previous studies [ 38 , 39 ] that have shown that vaping is by no means a safe replacement for smoking.…”
Section: Discussionsupporting
confidence: 91%
“…In 4 cases vaping precipitated a pneumothorax [52][53][54] and in 2 exacerbated pre-existing asthma [55]. Other diagnoses included eosinophilic pneumonia (n = 4) [56][57][58][59], combination of organizing and lipoid pneumonia (n = 3) [40], hypersensitivity pneumonitis (n = 3) [46,60,61], diffuse alveolar hemorrhage (DAH) (n = 1) [62], acute respiratory distress syndrome (ARDS) (n = 1) [63], a combination of ARDS, organizing pneumonia and diffuse alveolar damage (DAD) (n = 1) [64], epiglottitis (n = 1) [65], and a possible EVALI on asthma grounds (n = 1) [46].…”
Section: Classification Of Casesmentioning
confidence: 99%
“…Another case report of a young person who vaped cannabis oil described symptoms of catatonia, mania, and psychosis supposedly induced by previous cannabis vaping [ 151 ]. Cases of eosinophilic pneumonitis, synthetic cannabinoid intoxication, Torsades de pointes, and cardiac arrest were reported among youth who vaped various forms of marijuana [ 155 , 160 162 ]. A qualitative study which interviewed cannabis vaping youth reported participants describing the physical health effects ranging from respiratory, oral, nausea, and appetite related and headaches [ 157 ].…”
Section: Resultsmentioning
confidence: 99%